Generator DC 12 VOLT dengan Kapasitas 270 Watt untuk PLTMH Dijalan Bintara Sungai Duren Kecamatan Jambi Luar Kota Kabupaten Muara Jambi - Myson Myson; Anwar Aritonang (Universitas Batanghari Jambi, 2019)
Electricity energy needs are increased annually, so utilization of renewable energy sources is required as an alternative source of energy. To Progood Power then selected DC Permanent Magnet generator, permanent magnet generator has good efficiency in low round and the Cros flow turbine can work on not too high discharge. The DC Generator is used as a small scale PLTMH plant that uses hydropower as its movement. This small-scale Microhydro generator can generate 270 watts of power with the voltage coming out of the 12-18 Volt generator.